Deconstructing Affects and Affects of Deconstruction. Issue 2 (November 2019) - Zappa, Joseph
Abstract : Countering the common assumption in affect theory that deconstruction is incompatible with studies of affect, this essay theorises a deconstructive approach to reading for affect in texts and examines the role affect has always played in deconstructive reading. It reads Derrida alongside Deleuze who has been influential in affect theory in order to explicate what deconstruction adds to existing poststructural theories of affect: namely, how affect functions at the scene of reading, shaping the reading itself and coming into view through textual forms. In its second half, the essay turns to Cixous' 'Savoir, ' demonstrating through a reading of that text what a deconstructive reading of affect looks like in practice and exploring the ethics of such an approach.